(untitled) - Phan, Nguyễn Hồng (Thailand, 1993)
Contents: Distribution of mangroves in vietnam; biological and ecological parameters; geographical distribution; human impact on the mangrove ecosystem.
Keywords: Mangrove plants; Vietnam